The relationship between nurses' professional commitment and missed nursing care: a cross-sectional study in Iran - Mohammad Javad Ahmadzadeh-Zeidi; Zahra Rooddehghan; Shima Haghani (BMC, 2024)
Abstract Background & aims Missed nursing care is a global challenge that can have many consequences and it's known as a common threat to the patient safety and quality of nursing care. The nurses' professional commitment plays the final role in the occurrence of this issue. This study aimed to investigate the relationship between nurses' professional commitment and missed nursing care in Iran. Materials & methods This cross-sectional descriptive-analytical study was conducted on 270 nurses working in two hospitals affiliated to Tehran University of Medical Sciences (Sina & Shariati) from September to December 2023. The research community included all nurses working in medical-surgical wards in the designated hospitals. The research samples were included in a targeted and quota method after obtaining organizational permits, ethical approval and informed consent. Data collection was done using three questionnaires including demographic information form, Nursing Professional Commitment Scale, and MISSCARE Questionnaire. The collected data was analyzed in SPSS software, version 25. Results The results of Pearson's correlation test showed that there is a significant negative relationship between nurses' professional commitment and missed nursing care scores (r=-0.23) (p < 0.001). The mean score of nurses' professional commitment was reported at a moderate to high level (83.72 ± 16.02) and the mean score of missed nursing care was reported at a low level (47.84 ± 16.48). Nurses over 40 years old, morning shift and employed nurses showed higher professional commitment. Also, nurses under 29 years old and male nurses had more missed nursing care other than their participants. No relationship was observed between other demographic variables with nurses' professional commitment and missed nursing care. Conclusion The results of this study showed that higher nurses' professional commitment leads to higher quality of care and less missed nursing care. Based on findings of this research, it is recommended for health care providers and nursing managers to adopt programs to increase nurses' professional commitment and consequently reduce missed nursing care.